Reconfiguring Da’wah in Digital Modernity: Engaging Generation Z in the Age of New Media - Saefulloh, Aris; Zalafi, Zahratika; Triyustino, Supriyadi (Fakultas Dakwah UIN Saizu Purwokerto, 2026)
The rapid expansion of digital platforms has generated unprecedented access to religious content, while simultaneously producing information overload, misinformation, and competition with non-beneficial content. This condition raises critical questions regarding how da’wah actors adapt their strategies and how Generation Z interprets religious messages within a saturated digital environment. The study aims to analyze the orientation, challenges, and strategic adjustments of contextual da’wah targeting Generation Z. A qualitative approach was employed using in-depth interviews with selected preachers and members of Generation Z, complemented by document analysis of digital da’wah content. Data were analyzed thematically to identify patterns in media use, message construction, and audience reception. The findings indicate that digital da’wah has shifted from a one-way transmission model to a dialogical and participatory format. Preachers actively utilize social media to create interactive spaces that connect Islamic teachings with the everyday realities of Generation Z. However, they face significant challenges related to algorithmic visibility, misinformation, and the dominance of entertainment-driven content. Effective strategies emphasize message clarity, contextual relevance, and value-based engagement without compromising core Islamic principles. These results demonstrate that generational context and digital infrastructures substantially reshape the orientation and practice of contemporary da’wah.